Genetically Modified Neural Stem Cells for a Local and Sustained Delivery of Neuroprotective Factors to the Dystrophic Mouse Retina. (28th October 2013) - Jung, Gila; Sun, Jing; Petrowitz, Bettina; Riecken, Kristoffer; Kruszewski, Katharina; Jankowiak, Wanda; Kunst, Frank; Skevas, Christos; Richard, Gisbert; Fehse, Boris; Bartsch, Udo
Abstract : In two mouse models of retinitis pigmentosa, intravitreal transplantations of adherently cultivated neural stem cells that had been modified to secrete ciliary neurotrophic factor resulted in a sustained delivery of functionally relevant quantities of the cytokine to the dystrophic retina. These transplantations may thus represent a useful method for preclinical studies aimed at evaluating the therapeutic potential of a cell‐based administration of neurotrophic factors in mouse models of photoreceptor degeneration. Abstract : A continuous intraocular delivery of neurotrophic factors (NFs) is being explored as a strategy to rescue photoreceptor cells and visual functions in degenerative retinal disorders that are currently untreatable. To establish a cell‐based intraocular delivery system for a sustained administration of NFs to the dystrophic mouse retina, we used a polycistronic lentiviral vector to genetically modify adherently cultivated murine neural stem (NS) cells. The vector concurrently encoded a gene of interest, a reporter gene, and a resistance gene and thus facilitated the selection, cloning, and in vivo tracking of the modified cells. To evaluate whether modified NS cells permit delivery of functionally relevant quantities of NFs to the dystrophic mouse retina, we expressed a secretable variant of ciliary neurotrophic factor (CNTF) in NS cells and grafted the cells into the vitreous space of Pde6b rd1 and Pde6b rd10 mice, two animal models of retinitis pigmentosa. In both mouse lines, grafted cells attached to the retina and lens, where they differentiated into astrocytes and some neurons. Adverse effects of the transplanted cells on the morphology of host retinas were not observed. Importantly, the CNTF‐secreting NS cells significantly attenuated photoreceptor degeneration in both mutant mouse lines. The neuroprotective effect was significantly more pronounced when clonally derived NS cell lines selected for high expression levels of CNTF were grafted into Pde6b rd1 mice. Intravitreal transplantations of modified NS cells may thus represent a useful method for preclinical studies aimed at evaluating the therapeutic potential of a cell‐based intraocular delivery of NFs in mouse models of photoreceptor degeneration.